Functional analysis of anomeric sugar kinases. (2nd September 2016) - Conway, Louis P.; Voglmeir, Josef
Abstract: Anomeric sugar kinases perform fundamental roles in the metabolism of carbohydrates. Under- or overexpression of these enzymes, or mutations causing functional impairments can give rise to diseases such as galactosaemia and so the study of this class of kinase is of critical importance. In addition, anomeric sugar kinases which are naturally promiscuous, or have been artificially made so, may find application in the synthesis of libraries of drug candidates (for example, antibiotics), and natural or unnatural oligosaccharides and glycoconjugates. In this review, we provide an overview of the biological functions of these enzymes, the tools which have been developed to investigate them, and the current frontiers in their study. Graphical abstract: